2017
DOI: 10.1523/jneurosci.0681-17.2017
|View full text |Cite
|
Sign up to set email alerts
|

Increased GSNOR Expression during Aging Impairs Cognitive Function and Decreases S-Nitrosation of CaMKIIα

Abstract: As the population ages, an increasing number of people suffer from age-related cognitive impairment. However, the mechanisms underlying this process remain unclear. Here, we found that S-nitrosoglutathione reductase (GSNOR), the key enzyme that metabolizes intracellular nitric oxide (NO) and regulates S-nitrosation, was significantly increased in the hippocampus of both aging humans and mice. Transgenic mice overexpressing GSNOR exclusively in neurons showed cognitive impairment in behavioral tests, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 75 publications
1
20
1
Order By: Relevance
“…S-nitrosation of these protein targets is involved in mitochondrial fission, synaptic dysfunction, protein misfolding and ER stress ( 25 ). Our previous work has also revealed the important role of S-nitrosated modified protein targets, including ATG4B, HDAC2 and CaMKIIα, in neurotoxicity, neuronal differentiation and age-related cognitive impairment ( 28 , 63 , 64 ). S-nitrosation of mitochondrial ThrRS has been shown to transpire naturally in vivo in multiple mouse tissues, including the cortex, liver and heart.…”
Section: Discussionmentioning
confidence: 95%
“…S-nitrosation of these protein targets is involved in mitochondrial fission, synaptic dysfunction, protein misfolding and ER stress ( 25 ). Our previous work has also revealed the important role of S-nitrosated modified protein targets, including ATG4B, HDAC2 and CaMKIIα, in neurotoxicity, neuronal differentiation and age-related cognitive impairment ( 28 , 63 , 64 ). S-nitrosation of mitochondrial ThrRS has been shown to transpire naturally in vivo in multiple mouse tissues, including the cortex, liver and heart.…”
Section: Discussionmentioning
confidence: 95%
“…This not only shows that the redox state is constantly changing throughout the life cycle but also that redox changes are different in different organelles. We have also shown that the expression of GSNOR increases in the aging brain of humans and mice, indicating that the level of NO also changes in these tissues with aging ( 113 ). Interestingly, some studies have found an increase in the total oxidant status (TOS) and total antioxidant capacity (TAC) during labor and delivery in humans ( 65 ) and livestock ( 18 ).…”
Section: Redox Statusmentioning
confidence: 88%
“…Moreover, NO was neuroprotective in various animal models of Parkinson Disease, after oxygen-glucose deprivation or cerebral ischemia/reperfusion injury and this effect depended on a reduction in reactive oxygen species and protein S-nitrosylation in brain mitochondria 50 , 51 , while in a pharmacological study, neuroprotection occurred in a PI3K/Akt dependent manner 52 . Interestingly, NO-signaling deficiency may contribute importantly to age-related cognitive impairment 53 . In turn, and in accordance with our data, brain ischemia induced a deleterious elevation of NO and NOS in the hippocampus 54 .…”
Section: Discussionmentioning
confidence: 99%